1993
DOI: 10.2307/3578189
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Interactions in the Interphase Death of Irradiated Thymocytes

Abstract: The effect of the interaction of different types of cells on the interphase death and pycnosis of thymocytes irradiated in vitro was studied. When removed from the thymus suspension of cells with natural killer activity, medullary thymocytes and macrophages did not change the radiation-induced death of cortical thymocytes. On the other hand, postirradiation incubation of cortical thymocytes together with unirradiated thymocytes or with cells of certain other cell lines diminished thymocyte death. Mixing the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…This control confirmed that NDGA affects apoptosis via lipoxygenase inhibition. Taken together these data and the apoptosis prevention with the PLA2 inhibitor [5,14] 1, control; 2, 6 Gy; 3, 6 Gy+l gM indomethacin; 4, 6 Gy+10 gM indomethacin; 5, 6 Gy+100 I.tM indomethacin; 6, 6 Gy+20 gM NDGA; 7, 40 gM NDGA; 8, 6 Gy+40 gM NDGA. n = 3~.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…This control confirmed that NDGA affects apoptosis via lipoxygenase inhibition. Taken together these data and the apoptosis prevention with the PLA2 inhibitor [5,14] 1, control; 2, 6 Gy; 3, 6 Gy+l gM indomethacin; 4, 6 Gy+10 gM indomethacin; 5, 6 Gy+100 I.tM indomethacin; 6, 6 Gy+20 gM NDGA; 7, 40 gM NDGA; 8, 6 Gy+40 gM NDGA. n = 3~.…”
Section: Resultsmentioning
confidence: 59%
“…Previously we have shown that BPB, a PLA2 inhibitor [11], prevents nuclear pycnosis [5] and DNA fragmentation [14] in irradiated thymocytes. Nuclear pycnosis was the only criterion of the effects of lipoxygenase and cyclooxygenase inhibitors [5]. Nuclear pycnosis (or chromatin condensation) and intemucleosomal DNA fragmentation are *Corresponding author.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…During the progression of sepsis, thymic atrophy is induced via apoptosis (46). Because several reports suggest an involvement of PLA 2 in thymocyte apoptosis (47,48), the novel sPLA 2 might play a role in this process. The expression of novel sPLA 2 mRNA was also changed in rat lung after LPS treatment, but its pattern was different from the case of group IIA sPLA 2 .…”
Section: Molecular Cloning Of Novel Splamentioning
confidence: 96%